The Role of Scent-marking in Patchy and Highly Fragmented Populations of the Cabrera Vole (Microtus cabrerae Thomas, 1906) - Gomes, Luis (2014)
Rodent scent-marking is often used for territorial defense and self-advertisement, and both functions often entail the continuous scent-marking of a large area with high costs. In species with highly-fragmented populations and low density, in which the likelihood of social encounters is low,the costs of continuous scent-marking might exceed the associated fitness benefits; therefore, less intensive scent-marking only to signal presence to the opposite sex may be used. This hypothesis was tested in captivity with the Cabrera vole, a species with highly fragmented and low-density populations. Firstly, to assess the unknown scent-marking behaviour of the Cabrera voles, we conducted an assay wherein voles could scent-mark a clean substrate. Both sexes marked with urine and faeces, but never with anogenital secretions, and the amount of scent-marks was not different between sexes. In the subsequent assay, voles of each sex were given the choice of scent-mark on clean substrates or on substrates previously scent-marked by males or females. Both sexes marked with urine a larger area on substrates pre-marked by the opposite sex than on substrates pre-marked by the same-sex and clean substrates; however, no differences were found in the frequency of fecal boli deposited on the three types of substrate, and no anogenital secretions were found. The clear preference of receivers to scent-mark with urine the substrate pre-marked by the opposite sex strongly suggests that Cabrera voles use urine scent-marking for inter-sexual communication, probably to increase mate-finding likelihood, rather than for territorial defense and/or self-advertisement.